Dietary Lifestyle of Clinical Nutrition Students Compared with That of Age-Matched Non-Medical Students - Hakim, Noor A.; Alwagdany, Demah A.; Hammad, Jehan M.; Kattan, Maram F.; Mannan, Shahad A. (Current Nutrition & Food Science, 2022)
Background: There is an assumption that clinical nutrition (CLN) students should have better nutrition and health statuses and practice healthier lifestyles than other students. However, the effect of pursuing nutritional studies on student dietary lifestyle is not well known. Objective: To investigate differences in nutritional status between CLN-major and Administration/ Humanities-major (AHM) students as well as determine their sources of health and nutrition- related information. Methods: This is a descriptive and cross-sectional study in which CLN and AHM (mainly English and Arabic majors) students were recruited. Anthropometric measurements were taken, and a questionnaire was administered to assess their dietary lifestyle. Results: In total, 160 female students (CLN, 86; AHM, 74) participated in the study. Most students from both groups (>44%) were within the normal body mass index (BMI) range (18.5-24.9 kg/m2); no CLN students had class II or III obesity. No significant difference in BMI between the two groups was observed. CLN students tended to consume breakfast and snacks more than AHM students. Daily fruit and vegetable consumption was significantly higher among CLN than AHM students. No significant difference was found in fried food or water intake between the two groups. Additionally, CLN students were more involved in high-intensity exercise than their counterparts. Conclusion: Our findings suggest that health status and dietary lifestyle among CLN students are influenced by their study major. Obesity is less prevalent, and consumption of healthy foods, such as fruits and vegetables, is higher among CLN students. Future studies investigating the long-term effect of studying CLN on lifestyle and social relations with family and friends are warranted.
Keywords: health status